1993
DOI: 10.1128/mcb.13.12.7850
|View full text |Cite
|
Sign up to set email alerts
|

A mutant androgen receptor from patients with Reifenstein syndrome: identification of the function of a conserved alanine residue in the D box of steroid receptors.

Abstract: Reifenstein syndrome is an eponymic term that describes partial androgen-insensitive disorders. Androgen receptor isolated from five patients with this syndrome contains a specific mutation in the DNA binding domain of the receptor. This mutation converts an alanine to a threonine at position 596 next to the zinc catenation site at the second finger. The threonine 596 mutant receptor mediated normal androgen response at promoters with closely positioned multiple regulatory elements for the androgen receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…1B. The ZF2 dimer interface stabilizes receptor DNA binding to some but not all palindromic sites (7,18), whereas an ␣-helix within ZF1 intercalates into the major groove of the HRE and is essential for DNA binding (34,35). The above observations suggested that the receptor DBD and associated NLS are sufficient to mediate nuclear localization but not cluster formation.…”
Section: Fig 2 Transcriptional Activity Of Mr Wt and Mutant Fusion mentioning
confidence: 96%
See 2 more Smart Citations
“…1B. The ZF2 dimer interface stabilizes receptor DNA binding to some but not all palindromic sites (7,18), whereas an ␣-helix within ZF1 intercalates into the major groove of the HRE and is essential for DNA binding (34,35). The above observations suggested that the receptor DBD and associated NLS are sufficient to mediate nuclear localization but not cluster formation.…”
Section: Fig 2 Transcriptional Activity Of Mr Wt and Mutant Fusion mentioning
confidence: 96%
“…Moreover, the dimer interface mutations do not interfere with receptor-mediated repression, and the replacement of the wild type GR gene with a GR dimer mutant is non-lethal in mice in contrast to GR deletion, which is uniformly lethal (36,37). Hence, the disruption of the DBD dimer interface interaction surface imparts a complex phenotype, and the dimer mutants do not reflect the simple abrogation of DNA binding (7,18).…”
Section: Fig 2 Transcriptional Activity Of Mr Wt and Mutant Fusion mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that a mutation within the DBD dimer interface of AR has been implicated in the human disease, Reifenstein's syndrome (24). In transfection experiments, Kaspar et al found that the mutant AR was surprisingly unaffected by the mutation at paired HREs while its activity was decreased at a simple HRE.…”
Section: Fig 4 Heterodimer Formation By Ar and Gr Dbds In Vitromentioning
confidence: 99%
“…Mutations within the ligand binding domain may alter androgen binding but may, in addition, influence dimerisation due to disruption of N-C-terminal structural interactions (82)(83)(84). Mutations within the DNA binding domain have been demonstrated to affect receptor binding to target DNA (85). Mutations may also impair AR mRNA stability, leading to additional dysfunction of androgen action (86).…”
Section: Molecular Mechanisms Of Androgen Actionmentioning
confidence: 99%